Flexural Strength of Polymethyl Methacrylate Repaired with Fiberglass - Fariba Golbidi; Maryam Amini Pozveh (Tehran University of Medical Sciences, 2017)
Objectives: The purpose of this experimental study was to discover a method to increase the strength of repaired polymethyl methacrylate (PMMA) samples. Materials and Methods: In this experimental study, 40 specimens with the dimensions of 65×10×2.5mm3 were fabricated using heat-curing acrylic resin. Sixteen specimens were repaired with fiberglass and self-curing PMMA, while 16 samples were repaired with self-curing PMMA. Eight specimens were left intact as the control group. Afterwards, the flexural strengths of the repaired and intact specimens were measured by three-point bending test in a universal testing machine. Data were analyzed with one-way analysis of variance (ANOVA) and Tukey's HSD and LSD tests. The level of significance was set at P<0.05. Results: The mean flexural strength of the samples repaired with fiberglass was higher than that of the other repaired samples. However, the difference was statistically significant only with respect to the Meliodent group (P=0.008). Conclusions: Impregnated fiberglass could be used in the repair of denture bases to improve the flexural strength. In terms of the fracture site, it can be concluded that the lower flexural strength of the auto-polymerizing acryl compared to that of the heat-curing type was the main reason for the occurrence of fractures, rather than the weak bond between heat-curing and auto-polymerizing acrylic resins.